Hypopituitarism: A Very Rare Cause of Dilated Cardiomyopathy in a Child - Mandal, Anirban; Singh, Amitabh (Journal of Nepal Paediatric Society, 2018)
Dilated cardiomyopathy (DCMP), the leading type of cardiomyopathy in children, can be either a primary disease or secondary to a host of pathologies. Endocrine diseases are an extremely rare cause of DCMP in children. Hypopituitarism (congenital or acquired), a rare condition in children, may present in a variety of phenotypes depending on the hormonal deficiency (partial vs. pan hypopituitarism) and associated developmental defects. We describe a 10 year old boy with short stature, severely retarded bone age and congestive cardiac failure (CCF). He was diagnosed to have DCMP with hypopituitarism. Review of literature reveal possible mechanisms of DCMP and CCF in hypopituitarism and probably also indicate favorable response to hormonal replacement therapy.